Sosialisasi dalam Meningkatkan Motivasi Kewirausahaan dan Minat Berwirausaha Pada Ibu-Ibu UMKM dan PKK di Kelurahan Cisarua Kota Sukabumi - Rilla Sovitriana; Sularso Budilaksono; Nana Trinawati; Alifatqul Maulana (I-Com: Indonesian Community Journal, 2024)
Community service activities are carried out to socialize and increase entrepreneurial motivation and interest in entrepreneurship among MSME and PKK mothers in Cisarua Village, Sukabumi City. Based on the results of the questionnaire processed to MSME and PKK participants using the method. Results obtained: I was motivated to become an entrepreneur after receiving counseling from 30 respondents, 87% of my skill items increased after receiving training from 30 respondents, 87%. I asked to become an entrepreneur after receiving entrepreneurship training from 30 respondents 86%, my knowledge and skills increased after participating in training from 30 respondents 88%. I feel happy participating in entrepreneurial activities with 30 respondents 92%.